2022
DOI: 10.19080/crdoj.2022.16.555927
|View full text |Cite
|
Sign up to set email alerts
|

Family Social Support Perceptions and Medication Adherence among Elderly Diabetics in a Tertiary Health Institution in Lagos, Nigeria

Abstract: Background: The perception of family support is pivotal in improving the health and wellbeing of elderly individuals through adherence to medication especially among diabetics. This study investigated the relationship between perceptions of family social and medication adherence among elderly diabetic patients attending the outpatient clinics of the Lagos University Teaching Hospital (LUTH). Methodology: This was a cross sectional, hospital-based study carried out among 199 randomly selected elderly diabetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Both studies used the same family support assessment scale (PSS-Fa). [20,22] This trend is similar to findings among varied age groups of hypertensive patients in western Nigeria. [27 -29] The scores obtained with the perceived family support scale (PSS-Fa) are prone to inflation because the respondents may provide socially desirable responses.…”
Section: Figure 1: Reasons For Missing Doses Of Antihypertensive Medi...supporting
confidence: 81%
See 1 more Smart Citation
“…Both studies used the same family support assessment scale (PSS-Fa). [20,22] This trend is similar to findings among varied age groups of hypertensive patients in western Nigeria. [27 -29] The scores obtained with the perceived family support scale (PSS-Fa) are prone to inflation because the respondents may provide socially desirable responses.…”
Section: Figure 1: Reasons For Missing Doses Of Antihypertensive Medi...supporting
confidence: 81%
“…[22] However, some studies have shown that good medication adherence is better with family support. [20,27,35] This difference cannot be ascertained and may be explored in future research.…”
Section: Figure 1: Reasons For Missing Doses Of Antihypertensive Medi...mentioning
confidence: 97%
“…In the present study majority of study participants were females, married, newly diagnosed, with no hobbits which may be the reason for the hogher social support. This study finding is lower than the study conducted by Ayonote Uzoramaka Angela et al 28 and Iloh & Amadi 29 (77.5%). This difference in observation was due to the study setting, the present study was community-based study compare to previous studies 28,29 which have been conducted in hospitals.…”
Section: Discussioncontrasting
confidence: 71%
“…This study finding is lower than the study conducted by Ayonote Uzoramaka Angela et al 28 and Iloh & Amadi 29 (77.5%). This difference in observation was due to the study setting, the present study was community-based study compare to previous studies 28,29 which have been conducted in hospitals.…”
Section: Discussioncontrasting
confidence: 71%
“…Previous quantitative studies have shown that social support was essential to medication adherence in the senior population [ 17 20 ]. However, there was scarcely discussion on how seniors perceived and received social support and how understanding that support could equip pharmacists for their practice.…”
Section: Introductionmentioning
confidence: 99%